Occurrence of Cucumber mosaic virus Subgroups IA and IB Isolates in Tomatoes in Nigeria - Kayode, Adedeji; Odu, B. O.; Ako-Nai, K. A.; Alabi, Olufemi J. (journal of Plant Disease, 2023)
plant disease ;, Volume 98, Number 12,page 1750